2018
DOI: 10.3389/fimmu.2018.01404
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Human Eosinophils

Abstract: Immune cells face constant changes in their microenvironment, which requires rapid metabolic adaptation. In contrast to neutrophils, which are known to rely near exclusively on glycolysis, the metabolic profile of human eosinophils has not been characterized. Here, we assess the key metabolic parameters of peripheral blood-derived human eosinophils using real-time extracellular flux analysis to measure extracellular acidification rate and oxygen consumption rate, and compare these parameters to human neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 46 publications
2
48
0
1
Order By: Relevance
“…The authors measured maximal glycolytic capacity which they reported to be increased after hypoxia but again they did not measure reserve capacity and, unlike in this study, only looked at total ECAR rather than non-glycolytic and glycolytic ECAR. A loss of mitochondrial spare respiratory capacity after hypoxia has also been reported in CD4+ T cells, eosinophils, and neutrophils [ 39 , 40 ]. In these studies, glycolytic reserve capacity was not lost in CD4+ T cells; however, non-glycolytic ECAR was not taken into account or was not reported in eosinophils and neutrophils.…”
Section: Discussionmentioning
confidence: 96%
“…The authors measured maximal glycolytic capacity which they reported to be increased after hypoxia but again they did not measure reserve capacity and, unlike in this study, only looked at total ECAR rather than non-glycolytic and glycolytic ECAR. A loss of mitochondrial spare respiratory capacity after hypoxia has also been reported in CD4+ T cells, eosinophils, and neutrophils [ 39 , 40 ]. In these studies, glycolytic reserve capacity was not lost in CD4+ T cells; however, non-glycolytic ECAR was not taken into account or was not reported in eosinophils and neutrophils.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, enhancing AT eosinophil abundance is debated since several studies demonstrated no beneficial or even negative outcomes of this approach (220). Required for the production of ROS LPS-treated mouse bone marrow-derived neutrophils treated with Antimycin A or myxothiazol (190) Required for migration Polg CRISPR/Cas9-mediated neutrophil-specific knockout in Zebra fish (191) Pentose phosphate pathway ⇑ Required for NETosis Amyloid fibril-and phorbol myristate acetate-stimulated human neutrophils (192) Required for ROS generation and NETosis G6PD-deficient patients G6PD-deficient mice (193,194) TCA cycle ⇑ Required for chemotaxis Isocitrate dehydrogenase 1 mutant mice (195) Required for differentiation Mouse Atg5-deficient neutrophils and an in vitro model of differentiating neutrophils (196) Lipogenesis ⇑ Required for differentiation Atg7-deficient neutrophil precursors (197) Required for neutrophil maintanence FASlox/lox-Rosa26-CreER mice (198) Glutamine metabolism It was suggested that circulating eosinophils display a greater metabolic flexibility in comparison to neutrophils (200,201). Further investigation into the metabolic rewiring of eosinophils (shown in Table 3) is required as emerging roles of eosinophils suggest a central modulatory function in AT homeostasis.…”
Section: Eosinophilsmentioning
confidence: 99%
“…This inverse relationship seemed to be majorly driven by the degree of eosinophilic inflammation (and PEC) and BZH. We hypothesize that a combination of increased glycogen uptake by the large numbers of eosinophils, abundance of immature epithelial cells in basal zone with lower amounts of cytoplasm and cytoplasmic glycogen, and ongoing metabolic activity related to the eosinophilic inflammation ( 23 ) in epithelial (and possibly in subepithelial) compartment might explain these findings. The intensity of Raman peaks assigned to lipid content in iEoE was higher than that of aEoE but comparable with that of non-EoE controls.…”
Section: Discussionmentioning
confidence: 97%